Thermal barrier coatings - Xu, Huibin; Guo, Hongbo (Woodhead Pub Ltd., 2011)
Annotation Effective coatings are essential to counteract the effects of corrosion and degradation of exposed materials in high-temperature environments such as gas turbine engines.Thermal barrier coatingsreviews the latest advances in processing and performance of thermal barrier coatings, as well as their failure mechanisms.Part one reviews the materials and structures of thermal barrier coatings. Chapters cover both metallic and ceramic coating materials as well as nanostructured coatings. Part two covers established and advanced processing and spraying techniques, with chapters on the latest advances in plasma spraying and plasma vapor deposition as well as detonation gun spraying. Part three discusses the performance and failure of thermal barrier coatings, including oxidation and hot-corrosion, non-destructive evaluation and new materials, technologies and processes.
Keywords: Protective coatings.; Thermal barrier coatings.; elektronické knihy; electronic books